CTNI-11. CC-115 IN NEWLY DIAGNOSED MGMT UNMETHYLATED GLIOBLASTOMA IN THE INDIVIDUALIZED SCREENING TRIAL OF INNOVATIVE GLIOBLASTOMA THERAPY (INSIGHT): A PHASE II RANDOMIZED BAYESIAN ADAPTIVE PLATFORM TRIAL. (9th November 2020) - Rahman, Rifaquat; Trippa, Lorenzo; Fell, Geoffrey; Lee, Eudocia; Arrillaga-Romany, Isabel; Touat, Mehdi; McCluskey, Christine; Brunno, Jennifer; Gaffey, Sarah; Drappatz, Jan; Lassman, Andrew; Galanis, Evanthia; et al.
Abstract: BACKGROUND: CC-115 is an oral, CNS-penetrant, selective inhibitor of mammalian target of rapamycin kinase (mTOR) and deoxyribonucleic acid-dependent protein kinase (DNA-PK). Both targets are important in glioblastoma; PI3K/Akt/mTOR signaling is hyperactive in most glioblastomas, and DNA-PK is integral to repair of radiotherapy-mediated DNA damage. To investigate CC-115 in newly diagnosed glioblastoma and explore potential genomic biomarker associations, CC-115 was evaluated in the Individualized Screening Trial of Innovative Glioblastoma Therapy (INSIGhT) trial, an adaptive platform trial designed to efficiently test experimental agents. METHODS: Adults with newly diagnosed MGMT-unmethylated glioblastoma, with genomic data available, are eligible for this ongoing trial. Patients are adaptively randomized to one of several experimental arms or the control arm: standard radiotherapy with concurrent and adjuvant temozolomide. The primary endpoint is overall survival (OS). Patients randomized to CC-115 (10mg po BID) received it concurrently with radiotherapy and as adjuvant monotherapy. As the first in-human use of CC-115 with radiation, a safety lead-in 3 + 3 design was used. RESULTS: Twelve patients were randomized to CC-115; seven patients had possible treatment-related CTCAE grade > 3 toxicity, including four pre-specified dose-limiting toxicities: liver function abnormality (n=1), hyperlipidemia (n=1), lipase elevation (n=1) and cerebral edema (n=1). There was no significant difference in progression-free survival (PFS, median 4.2 months [CC-115] vs. 5.2 months, p=0.9) or OS (median 10.1 months [CC-115] vs. 14.5 months, p=0.9) compared to the 50 patients randomized to the control arm. Based on early PFS results, randomization probability to CC-115 decreased from 25% to < 10% at time of the trial arm closure. CONCLUSION: Concurrent and adjuvant CC-115 was associated with toxicity and failed to improve PFS or OS. The INSIGhT trial design allowed for more efficient testing of CC-115, decreasing patients and resources allocated to a therapy that was discontinued due to concerns about toxicity and unfavorable risk-to-benefit ratio.